An Analysis of Politeness in Language in Early Childhood "A Case Study of the Habit of Listening to Dangdut Koplo Songs in Pudak Wetan Ponorogo" - Eka Widyana; Ida Yeni Rahmawati; Muhibbudin Fadhli (JURNAL INDRIA (Jurnal Ilmiah Pendidikan Prasekolah dan Sekolah Awal), 2020)
Early childood is a group of children who are in the process of growth and development. As the development of the era, children like to imitate something that’s being viral both on television and on social media. Something that is viral today, among others, is dangdut koplo music. Dangdut koplo music is currently enjoyed by public. This has a negative effect on children’s politeness in language because the lyrics are rough and not educating. This study aimed to determine the negative effects of listening to dangdut koplo songs for early childhood. This research was conducted in the village of Pudak Wetan, Ponorogo Regency. This research used descriptive qualitative with a case study method. Validity data technique used source triangulation and triangulation method to explore the truth of information through observation and Interview. The observation was conducted with children and society around the neighborhood, whereas the interview was conducted with children, parents, and environment around the neighborhood. The results of this study proved that many children in Pudak Wetan Ponorogo Village who used to listen to  Koplo songs became rude when talking. The language they used became  rude and inappropriate. Dirty words were often used by these children. Even apprently they did not have appropriate manner towards the elder. Children memorized and mastered Koplo songs more rather than educating songs for children. Therefore, the habits of listening to Koplo songs gave negative impacts on politeness in language in early childood.